Predicting pre-service English language teachers’ intentions to use augmented reality - Karacan, Cemil Gökhan; Polat, Mustafa (Routledge, 2022)
Augmented Reality (AR) is a new-generation technology that shows video, picture, and animated 3 D objects over real-life scenes. Despite AR’s prevalence around the world, language teacher education programs are not prompt in the integration of digital educational tools. The present study explored the factors that predict pre-service English teachers’ intentions to use AR in their future language classes. For this purpose, a correlational research design was applied. The participants were exposed to an implementation process which included training on creating AR experiences as well as developing a stand-alone AR application and a discussion session on AR in language classes. Next, a 5-point Likert-type scale of Decomposed Theory of Planned Behavior (DTPB) was administered to pre-service English teachers (n = 141). Results indicated that attitude with a very high impact from perceived usefulness was the most significant predictor of participants’ intentions to use AR. On the other hand, facilitating conditions and ease of use were the least impactful factors. The findings offer implications for teacher educators, curriculum designers, teacher education program developers and teachers.
Keywords: Augmented Reality; Pre-Service English Teachers; Decomposed Theory of Planned Behavior; Usage Intention